2017
DOI: 10.1109/tsp.2017.2706186
|View full text |Cite
|
Sign up to set email alerts
|

Filtering Random Graph Processes Over Random Time-Varying Graphs

Abstract: Abstract-Graph filters play a key role in processing the graph spectra of signals supported on the vertices of a graph. However, despite their widespread use, graph filters have been analyzed only in the deterministic setting, ignoring the impact of stochasticity in both the graph topology as well as the signal itself. To bridge this gap, we examine the statistical behavior of the two key filter types, finite impulse response (FIR) and autoregressive moving average (ARMA) graph filters, when operating on rando… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 44 publications
1
67
0
Order By: Relevance
“…is a rational function, g(T) can be defined in two ways. First, by (2), and second by compositions, linear combinations, and inversions, as…”
Section: Spectral Graph Filtersmentioning
confidence: 99%
See 1 more Smart Citation
“…is a rational function, g(T) can be defined in two ways. First, by (2), and second by compositions, linear combinations, and inversions, as…”
Section: Spectral Graph Filtersmentioning
confidence: 99%
“…Since the eigendecomposition is not stable to perturbations in the topology of the graph, this result does not prove robustness to such perturbations. [2] showed that the expected graph filter under random edge losses is equal to the accurate output. However, [2] did not bound the error in the output in terms of the error in the graph topology.…”
Section: Introductionmentioning
confidence: 99%
“…. , λ N −1 of W appear as coefficient in (16). Thus, the difference between the largest and smallest coefficients in each equation in (16) can be quite significant.…”
Section: A Gma Filtermentioning
confidence: 99%
“…, λ N −1 of W appear as coefficient in (16). Thus, the difference between the largest and smallest coefficients in each equation in (16) can be quite significant. Moreover, the difference between coefficients in (16) for the case of true A compared to the case of mismatched W can be also significant.…”
Section: A Gma Filtermentioning
confidence: 99%
See 1 more Smart Citation